ISLAMIC FINANCIAL PRODUCTS AND THEIR CONTRIBUTION TO THE GROWTH OF SMES IN HARGEISA, SOMALILAND - Habtamu Alebachew Legass; Hudayfe Said Ahmed (Sharia Oikonomia Law Journal, 2025)
This study explores the impact of Islamic financing products, specifically Musharakah and Murabahah, on the growth of small and medium enterprises (SMEs) in Hargeisa, Somaliland. With an increasing demand for Shariah-compliant financing, the research highlights how these products contribute to the financial stability, operational efficiency, and business relationships of SMEs. A survey of 100 SMEs revealed that 90% expressed interest in Islamic financial products, yet 90% were dissatisfied with the current offerings, citing a lack of tailored products and high costs, particularly with Murabahah. The study further examined the role of Musharakah in fostering long-term growth through risk-sharing and strategic support, but also identified challenges such as complexity and limited availability. Murabahah, with its fixed cost structure, was found to be more popular, offering immediate access to capital but also creating financial strain due to high markup rates. The findings suggest a need for more diverse, flexible, and cost-effective Islamic finance options, as well as greater awareness and understanding of these products. The study concludes by recommending the expansion of Islamic finance offerings and further research into the long-term effects of these financing models on SME sustainability in emerging markets.